Gamma irradiation of fruits - Beyers, Marguerite (Department of Physics, 2026)
At a Joint FAO/tAEA/WHO Expert Committee on Food Irradiation (JECFI) meeting held in 1976, recommendations were made to rationalize the unnecessarily elaborate wholesomeness. evaluation procedures for irradiated foodstuffs: inter a/ia, that (a) for irradiation doses up to 5 kGy, radiation-chemical results together with animal feeding studies would eventually lead to the general acceptance of irradiated food, (b) wholesomeness data could be extrapolated from a representative foodstuff to foods in the same diet class, and (c) a purely chemical approach to wholesomeness evaluation would be contemplated if enough data could be accumulated. Following these guidelines, a chemical investigation into the wholesomeness of y-irradiated fruit with special emphasis on the mango was undertaken. Irradiation at the commercially recommended doses did not adversely affect the constituents of mangoes. papayas, litchis and strawberries at the edible-ripe stage, nor could changes which could be attributed to irradiation be detected in irradiated mangoes and papayas as the fruits ripened. The conventional preservation method of canning and the storage of frozen fruit were more detrimental to the nutritional value of the fruits than irradiation. The chemical composition of the four fruits was sufficiently similar for them to be grouped into the same diet class. These favourable radiation-chemical results justified the development of a theoretical model mango which could be used for extrapolation of wholesomeness data from an individual fruit species to all others within the same diet class. Several mathematical models of varying orders of sophistication were evolved. In all of them, it was assumed that the radiant energy entering the system reacted solely with water. The extent of the reaction of the other components of the model fruit with the primary water radicals was then determined. No matter which mathematical treatment was employed, it was concluded that the only components which would undergo significant modification would be the sugars. Furthermore, by the application of radiation-chemical knowledge to these results, the only toxic radiolysis products formed in significant quantities would be the carbonyls derived from the sugars, but these carbonyls would be nonmutagenic in the fruit. These predictions were verified experimentally in the so-called "synthetic" mango (an aqueous solution of the components of the model mango) and in Kent mangoes both as to carbonyl yields and carbonyl nonmutagenicity in the fruits and as to the protective influence of the sugars on the degradative behaviour of certain selected components of the mango. In order to extrapolate these data from the mango to other fruits, mathematical models of three fruits containing less sugar than the mango, viz. the strawberry, tomato and lemon, were compiled. With these models, the conclusion was reached that the theoretical degradation spectra of these fruits were qualitatively similar to the degradation pattern of the model mango. The protective effect of the sugars diminished with decreasing sugar concentration. No additional mutagenic radiolysis products were predicted. It was also estimated that the radiolysis products would be nontoxic. Theory was again substantiated by the practical demonstration of the protective effect of the sugars in the tomato and lemon. The decrease in radiation damage was enhanced by the mutu.a.1 protection of the components of the whole synthetic fruits with ultimate protection being afforded by the biological systems of the real fruits. Therefore, the radiation-chemical behaviour of fruits was essentially similar, so that extrapolation of wholesomeness data from one fruit to another would be possible. This "chemiclearance" concept formed part of the evidence which enabled the 1981 JECFI meeting to arrive at the conclusion that the irradiation of any food commodity up to 1 0 kGy presents no toxicological hazard, so that toxicological testing of such foods would no longer be necessary.